ANATOMICAL EVIDENCE FOR REINSTATING SCHIZOSTACHYUM LONGISPICULATUM AND S. BIFLORUM - SUHARDJONO PRAWIROATMODJO (BRIN Publishing (Penerbit BRIN), 1982)
Based on the differences in their leaf anatomy, it is suggested that S. longispiculatwm, S. biflorum and S. blumei, should be considered as three distinct species.